Comparison of laparoscopic partial nephrectomy performed with AirSeal® system vs. standard insufflator: results from a referral center - Forte, Flavio; Tripodi, Domenico; Pironi, Daniele; Corongiu, Emanuele; Gagliardi, Federica; Frisenda, Marco; Gallo, Gaetano; Quarantiello, Antonia; Di Lorenzo, Giuseppe; Cavaleri, Yuri; Salciccia, Stefano; Lori, Eleonora; et al. (Frontiers in Surgery, 2023)
Objective To compare perioperative and oncologic surgical outcomes during laparoscopic partial nephrectomy (LPN) performed by standard carbon dioxide insufflation, with those from surgeries in which the AirSeal® intelligent insufflation system was used for renal tumors. Materials and methods A total of 27 patients with renal tumor were identified, 14 underwent LPN with AirSeal® (group A) and 13 LPN with standard insufflator (group B), respectively. Demographic baseline characteristics were similar in the two groups. Results The size of the tumor was largest in group B (29.64 vs. 32.1 mm). The mean operative time was shorter in the AirSeal® group [group A: mean 109.0 min, median 107.5 min, interquartile range (IQR) 85; group B: mean 121.0 min, median 120.0 min, IQR 50.0]. Positive margin rates were absent in the two groups. Estimated blood loss presented a difference in the perioperative period (group A: mean 1.5 g/dL, median 1.45 g/dL; group B: mean 2.15 g/dL, median 2.2 g/dL). Time to ischemia was found to be shorter in group A with a median of 18 min compared to a median of 20 min in group B. No subcutaneous emphysema, pneumothorax, and pneumomediastinum cases occurred in either group. A postoperative complication developed in one patient requiring superselective embolization. Conclusion In selected patients, our preliminary surgical experience has shown that the LPN procedure performed with the aid of the AirSeal® intelligent insufflation system can be used to treat even medium-/high-complexity kidney lesions, with a reduction in operating times, lower rates of complications, and perioperative blood loss. Clinical trial registration AirSealV1.